Processos eletrolíticos e de nanofiltração para produção de água de reúso a partir de efluentes de laticínios - Nadal, Bruno Alves (2018)
Dairy production in Brazil was approximately 24 billion litres in the year 2015, with 900 million litres benefited in Rio Grande do Sul. This number represents a production growth in the state of 5.1%. The volume generated in wastewater from dairy products can range from 0.2 to 10 litres per litre of processed milk, being a potential polluting source due to the high organic load, thus hindering the removal of pollutants by conventional treatment processes. On the other hand, these effluents have a high potential for reuse due to large volumes of water constituents, provided they are properly treated. The objective of this work is to study the technical feasibility of applying the eletroxidação technique and associated with the process of separation of the membrane for the treatment of effluents generated in dairy products, obtaining as a result water with enough drinking to reuse in the source process. For this, a synthetic effluent was developed, characteristic of the processing industry of varied products (cheese, yogurt, butter). A study was carried out on the pH behavior and the currentdensity variables for the electrolytic process and the nanofiltration was applied as a way to complement the treatment and the production of reusable water. The best experimental condition of the organic load removal was pH 5.0 and current density 100 am-2. The Eletroxidação followed the results of the efficiency of removal and operating costs near conventional treatment. The electrolytic process presents advantages, since it uses a shorter treatment time compared to the conventional area, smaller for the installation and reduction of the workforce for the operation. The nanofiltration made it possible to obtain a permeation with characteristics close to the beverage in various analytical parameters, with cod of 69 mg/L, i.e., a pollutant removal of 98%, for the other analytical parameters, there was 100% in the efficiency of removing them. Thus, electrolytic processes associated with nanofiltration can be used as substitutes for conventional treatments and produce water that can be reused in the industrial process, aiming at hydro sustainability.